(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article analyzes the process of globalization and problems in the formation of sociocultural reality. Globalization in new sociocultural, political and economic spaces is increasingly being implemented in all countries of the world, losing the fundamental principle of existence, cultural values, ideals and norms that are directly related to human life, as the main engine of globalization. In reality, it is necessary to analyze how countries are the engines of economics and politics, in the process of realizing their interests in the process of globalization.